Expanding the cleft phenotype: the dental characteristics of unaffected parents of Australian children with non‐syndromic cleft lip and palate. Issue 4 (17th November 2013) - Aspinall, Andrea; Raj, Supriya; Jugessur, Anil; Marazita, Mary; Savarirayan, Ravi; Kilpatrick, Nicky
<x xml:space="preserve">Abstract</x> Background The aetiology of isolated clefts of the lip and/or palate remains obscure. Unaffected family members are treated as if their genetic risks are equivalent and low. Given the number of genes associated with both clefting and dental anomalies, the hypothesis that such anomalies contribute to the cleft phenotype should be explored. Aim To describe the dental characteristics of parents of children with non‐syndromic cleft lip ± palate. Design Unaffected parents of Australian children with a cleft of the lip ± palate underwent dental examination including radiographs, photographs, and impressions. Dental anomalies were identified. Results Data were available on 101 parents (49 males, 52 females). Fifty‐one participants had at least one dental anomaly. Twelve (11.8%) individuals had congenital absence of teeth, with seven missing multiple teeth. The tooth most commonly missing was the upper right lateral incisor. Five subjects (4.9%) had microdontia (upper lateral incisor most commonly affected). Four subjects (4.0%) had supernumerary teeth. Enamel defects were present in 27 (26.7%) cases with the incisors (46.8%) followed by premolars (24.2%) most affected. Conclusions This study supports previous work suggesting that 'unaffected' parents of children with clefts of the lip ± palate may present with dental anomalies.